Cognitive-motor exergame training on a labile surface in stroke inpatients: study protocol for a randomized controlled trial - Büttiker, Joel; Marks, Detlef; Hanke, Manuel; Ludyga, Sebastian; Marsico, Petra; Eggimann, Benjamin; Giannouli, Eleftheria (Frontiers in Neurology, 2024)
Background: Cognitive-motor training in form of exergames has been found to be feasible and effective for the improvement of motor and cognitive functioning in older adults and several patient populations. Exergame training under unstable conditions might increase the proprioceptive resources needed and thus might be a superior training approach compared to exergame training on stable ground for stroke patients, who often have proprioceptive deficits.Objective: Aim of this study is to assess the feasibility and effects of exergame-based cognitivemotor training on a labile platform on physical and cognitive functioning in stroke inpatients.Methods: This is two-armed pilot randomized controlled trial taking place in an inpatient neurologic rehabilitation clinic. A total of 30 persons that are undergoing inpatient rehabilitation due to a stroke will be randomly assigned to either the intervention group (IG) or the control group (CG). Participants of the IG will receive exergame-based motor-cognitive training on a labile surface, whereas participants of the CG will train on a stable surface. Primary outcome is feasibility comprising measures of adherence, attrition, safety and usability. Secondary outcomes will be measures of cognitive (psychomotor speed, inhibition, selective attention, cognitive flexibility, brain activity) and motor (functional mobility, gait speed, balance, proprioception) functioning.Results: Data collection started in February 2024 and is expected to be completed by August 2024.Conclusions: This is the first study looking into exergame training on labile surface in stroke patients. It will give valuable insights into the feasibility and potential added value of this type of training and thus inform further implementation efforts in the context of inpatient rehabilitation.